Analysis of financial management in the implementation of Minabua Village development, Mimika Regency - Asmara, Hario Pri; Marlissa, Elsyan R.; Urip, Transna Putra (Journal of Multidisciplinary Academic Business Studies, 2025)
Purpose: This study aimed to analyze financial management in the implementation of development in Minabua Village, Mimika Regency. The main focus is to evaluate the planning, implementation, and reporting of the village budget in line with the principles of transparency, accountability, participation, and effectiveness. Monitoring and evaluation of village funds are essential instruments for improving community welfare, with good financial management as a prerequisite for realizing sustainable village development. Methodology: A descriptive qualitative approach was employed using surveys, observations, in-depth interviews, and documentation studies. The informants included village officials and community leaders. Data were analyzed through reduction, presentation and conclusion drawing. Results: The findings indicate that financial management in the Minabua Village has shown progress. Planning has involved community participation through village deliberations but has not fully addressed the priority needs. Implementation demonstrates accountability and transparency; however, community participation remains limited. Reporting and accountability are constrained by the lack of technical capacity of village officials. Furthermore, monitoring and evaluation conducted by regional authorities are weak and largely administrative in nature. Conclusions: Although transparency and accountability in financial management are relatively strong, shortcomings in community participation and technical reporting hinder effective implementation. Stronger monitoring and evaluation mechanisms are required. Limitations: This study was limited to a single village and may not represent broader practices across Mimika Regency or Papua. Contribution: This study provides empirical insights into village financial management, offering policy-relevant recommendations to strengthen transparency, participation, and evaluation as foundations for improved village development outcomes.